Productive Zakat Sociopreneur as an Effort to Alleviate Poverty in Sustainable Development (SDGs): a Study on BAZNAS Surabaya City - Alfin Maulana; Fitryani; Hafidz Novantori; Nova Hardiansyah (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2024)
Introduction: This study analyzes the implementation of productive zakat distribution by BAZNAS in Surabaya and its role in achieving the Sustainable Development Goals (SDGs), focusing on poverty reduction and sustainable development through sociopreneurship. Methods: Using a qualitative descriptive approach, data were gathered via in-depth interviews, observations, and snowball sampling. The study examines collaborative efforts between BAZNAS, the Surabaya City Government, and local cooperatives. Results: The findings highlight the success of the Surabaya Berdaya program, which supports 17 zakat recipients through social entrepreneurship, reducing poverty and fostering sustainable development. Conclusion and Suggestion: The productive zakat sociopreneur program effectively advances the SDGs by alleviating poverty and empowering communities. Future efforts should enhance collaboration and scalability to maximize its impact.